268An online survey of sexual health, knowledge and behaviour of young South Australians. (2nd September 2021) - Harfield, Stephen; Elliott, Salenna; Housen, Tambri; Ward, James
Abstract: Background: Since 2010 rates of sexually transmitted infections (STIs-chlamydia, gonorrhoea and syphilis) have been increasing among young Australians. Most STIs are diagnosed in young people aged 16-29 and rates of diagnosis are higher among Aboriginal people than non-Aboriginal people. Little information exists to understand social and behavioural issues associated with increasing rate of STIs, especially in South Australia and among Aboriginal peoples. Methods: We undertook an online cross-sectional survey of sexual health, knowledge and behaviour of young South Australians aged 16-29 years during a six-week period in 2019. Descriptive analysis, univariate and adjusted logistic regression models were used to compare Aboriginal and non-Aboriginal participants. Results: In total 2, 380 South Australians participated in the "Let's Talk About It" (LTAI-2019); 52% were female, the median age was 20 years (IQR:17-24) and 10% of participants identified as Aboriginal. Regression analysis suggested among both Aboriginal and non-Aboriginal participants being female (aOR 2.41, CI:1.07-3.51, & 3.03, 2.17-4.23 respectively) and not using a condom during last sexual encounter (2.33, 1.03-5.29 & 1.62, 1.15-2.27) were associated with ever being tested for an STI and having two or more sexual partners in the past 12 months (1.37, 0.67-7.45 & 3.13, 1.31-7.45) was associated with testing positive for an STI. Conclusions: LTAI-2019 is the first study to describe factors associated with STIs among young South Australians. It is evident that young people are engaged in behaviours which increase their risk of acquiring STIs. Public health action which considers these behaviours particularly those that target young Aboriginal people is required. Key messages: LTAI 2019 is the first study to describe current sexual health, knowledge, behaviours and access to health services for STIs and related issues amongst young South Australians. It provides evidence that is useful for informing both public health practice and policy, and the development of STIs preventative health programs.